Relative characterization of immobilized beta-glucosidase on calcium-alginate and acid functionalized-multiwalled carbon nanotubes peel - Jameel, Ahmad Tariq; Maalim, Kauthar Yusuf; Yusof, Faridah (Penerbit UTM Press, 2019)
Natural polymeric gel such as alginate and carrageenan, and carbon nanomaterials, especially MWCNT and graphene are gaining increasing popularity as immobilization support owing to their biocompatibility. Thus, this study attempts to make a relative characterization of the immobilized β-glucosidase on alginate and multiwalled carbon nanotubes (MWCNT) to assess their relative merits as biocatalyst. Acid functionalization of MWCNT lead to the formation of carboxyl groups at the MWCNT surface which seemed to have role in the stable attachment of the enzyme on the MWCNT surface. The effectiveness of the immobilized enzyme was evaluated using hydrolysis of p-nitrophenyl-β-D-glucopyranoside to p-nitrophenol. The optimum immobilization conditions were found to be 17 mg MWCNT and 4 h incubation time for MWCNT, and 3.5 wt% sodium alginate solution and 2 h incubation time for the Ca-alginate beads. The immobilization yield on MWCNT was found to be 96% and that for the Ca-alginate beads was 86%. The residual activity of the enzyme at the third cycle of subsequent reuse was 85% for the enzyme-MWCNT and almost 50% for the enzyme-alginate beads. Both, Ca-alginate and MWCNT immobilized enzyme were found to follow Michaelis-Menten kinetics. The kinetic data were best represented by the Langmuir plot. The kinetic constants V max and K m for the MWCNT immobilized enzyme were obtained as 1.324 mM/min and 0.801 mM, respectively, while for the alginate immobilized enzyme, the constants predicted were 1.240 mM/min and 0.524 mM, respectively. Thus MWCNT immobilized β-glucosidase exhibited greater stability in terms of activity and reusability compared to Ca-alginate beads.